Implementation of topsis method for decision support of department at SMKN 4 Surabaya - Dyahrizki Iswarani (IJEEIT : International Journal of Electrical Engineering and Information Technology, 2022)
Vocation high school has many skill programs. The skill program implemented at the Vocational High School adapts to the needs of the existing world of work. The skill program at the vocational level also adjusts to community and market demands. Vocational education is secondary education that prepares students especially to be ready to work in certain fields. Based on the information obtained, there are 4 majors that is Accounting, Office Administration, Multimedia, Online Business and Marketing and Travel Business. The skill program implemented at the Vocational High School adapts to the needs of the existing world of work. Metode Technique For Others Preference By Similarity To Ideal Solution (TOPSIS) as decision-making that lies in its ability to make more informed judgments because it is based on the predetermined criteria and preference weights (priority).